The Influence of Learning Styles, Learning Independence, Family Support, and School Environment on Academic Achievement with Learning Motivation as a Moderating Variable in 11th Grade/Fase F Economics Students - Muthia Uswatun Nisa; Desi Areva; Vivina Eprillison (Journal of Practice Learning and Educational Development, 2026)
This study aims to determine: 1) The influence of learning styles on student achievement at SMA N 13 Padang, 2) The influence of learning independence on student achievement, 3) The influence of family support on student achievement, 4) The influence of the school environment on student achievement, 5) Learning motivation strengthens the influence of learning styles on student achievement, 6) Learning motivation strengthens the influence of learning independence on student achievement, 7) Learning motivation strengthens the influence of family support on student achievement, 8) Learning motivation strengthens the influence of the school environment on student achievement.This type of research is quantitative. The population in this study were all 11th-grade students studying economics at SMA Negeri 13 Padang. Sampling used a stratified random sampling technique. The instrument used for the study was a closed questionnaire with Multiple Linear Regression test using SPSS software version 25.The results of the study showed that: 1) There is an influence between learning styles (X1) on learning achievement (Y) of class XI/F Phase students at SMA Negeri 13 Padang. For the regression coefficient value of the learning style variable (X1) of 0.239 which is positive with a calculated t value of 4.887> t table of 1.997 with a significant value of 0.000 <α = 0.05, 2) There is an influence between learning independence (X2) on learning achievement (Y) of class XI/F Phase. For the regression coefficient value of the learning independence variable (X2) of 0.454 which is positive with a calculated t value of 7.415> t table of 1.997 with a significant value of 0.000 <α = 0.05. 3) There is an influence between family support (X3) on the learning achievement (Y) of class XI/Phase F students (X3) of 0.135 which is positive with a calculated t value of 2.459> t table of 1.997 with a significant value of 0.017<α = 0.05. 4) There is an influence between the school environment (X4) on the learning achievement (X5) of class XI/Phase F students. For the regression coefficient value of the school environment variable (X4) of 0.064 which is positive with a calculated t value of 2.738> t table of 1.997 with a significant value of 0.008 <α = 0.05. 5) Learning motivation strengthens learning styles on the learning achievement of class XI/Phase F students. This can be seen from the results of data analysis, the R Square (R2) value in model II is greater than R2 model 1 (0.560>0.495). 6) Learning motivation strengthens learning independence and student achievement. This is evident from the data analysis, which shows that the R2 value in Model II is greater than the R2 value in Model 1 (0.704>0.630). 7) Learning motivation strengthens family support for student achievement in grade 1. This is evident from the data analysis, which shows that the R2 value in Model II is greater than the R2 value in Model 1 (0.394>0.391). 8) Learning motivation strengthens the school environment for student achievement in Grade 11/Phase F. This is evident from the data analysis, which shows that the R2 value in Model II is greater than the R2 value in Model 1 (0.527>0.525).